Phytoplankton community composition effects on phosphorus sedimentation dynamics in Lake Erie - Bruce Ronzio, Sunniva (University of Waterloo, 2007)
Cultural eutrophication is caused by the excess addition of phosphorus to aquatic ecosystems, and has long been a water quality management issue in Lake Erie. Despite successful reductions in external loading of phosphorus in Lake Erie the in lake total phosphorus (TP) concentrations are increasing recently and symptoms of eutrophication are apparent. In this study I examined the sedimentation velocity of particulate phosphorus and how it is affected by stratification and plankton community composition over the growing season. Diatoms had the highest sedimentation velocities and a shift to slower settling species with greater form resistance (Synedra sp. and Fragilaria sp.) was observed during the stratified period possibly in response to the shallower mixed layer. No significant variation in sedimentation velocity was found with trap depth, plankton size or temperature; hence the individual plankton cells were employing methods to change their sedimentation velocity in accordance with changing environmental conditions. Phosphorus sedimentation was most closely related to silica sedimentation, which largely represents the sedimentation of the diatoms. Thus any shifts in community composition will affect phosphorus-settling rates. The sedimentation rate of phosphorus decreased from June 2nd until August 26th during the stratified period at station84 and from June 2nd to August 5th at station 452. The decline of total phosphorus was less than the sedimentation rate, hence, sediment resuspension and redistribution from the littoral sediments along with atmospheric deposition are important sources of phosphorus to the central and eastern basins of Lake Erie. The sedimentation rates of P, N and C did not follow the Redfield ratio. The sedimentation velocity of P was much less than that of C and N, indicating that P is conserved in the epilimnion and possibly that C and sedimentation contains more non-living material. Therefore, modelling phosphorus sedimentation after carbon and nitrogen sedimentation is inappropriate. Laboratory sedimentation towers can be used to measure phytoplankton sedimentation velocity including net upward movement, which traditional sedimentation traps are unable to do. Determination of the sedimentation velocity of the phytoplankton community to variables such as light, temperature and nutrient status, using this method, may eventually lead to a dynamic phosphorus model that could more effectively reduce eutrophication effects in Lake Erie.
Keywords: phosphorus; sedimentation; Biology